A new genus of the family Nesticidae (Arachnida: Aranei) from the Caucasus - Fomichev, Alexander A. (Arthropoda selecta : русский артроподологический журнал)
A new genus, Daginesticus gen.n. with the type species, D. dzhamirzoevi sp.n. (male female) is described from the Caucasus based on morphological and molecular evidences. Three new combinations are proposed: Daginesticus mamajevae (Marusik, 1987) comb.n., Aituaria borutzkyi (Reimoser, 1930) comb.n. and Aituaria eriashvilii (Marusik, 1987) comb.n. (all ex. Carpathonesticus). The new genus is closely related to Aituaria Esyunin et Efimik, 1998 and has unreduced eyes and well-developed body pigmentation. Description, figures, diagnosis and photographs of the habitat are provided. The conformation of the male palp in Nesticini is discussed and new terms are suggested based on homology of different sclerites.